Health Literacy and Environmental Health Behaviors Related to Potential Microplastic Exposure Among Urban Residents in Thailand: A Cross-Sectional Study - Santisith Khiewkhern; Benchaphon Aengwanich; Chamnan Chinnasee; Supatra Noo-In; Chitkamon Srichomphoo; Ruchakron Kongmant; Le Ke Nghiep (Environments, 2026)
Microplastic contamination has become a major environmental health concern because of its widespread occurrence and potential risks to human health. Although environmental health literacy (EHL) is recognized as an important determinant of health-related decision-making, evidence regarding its influence on behaviors that reduce potential microplastic exposure remains limited, particularly in riverine communities of developing countries. This study assessed EHL, environmental health behaviors associated with potential microplastic exposure, and factors associated with these behaviors among urban residents living along the Mekong River in Thailand. A community-based cross-sectional study was conducted among 420 adults in Mueang Nakhon Phanom District, Thailand, between October and December 2024 using multistage random sampling. Face-to-face interviews were performed using a content-validated questionnaire assessing six EHL domains and environmental health behaviors related to microplastic exposure. Multivariable logistic regression was used to examine factors associated with poor environmental health behaviors. Overall, 41.7% of participants demonstrated good environmental health behaviors, whereas 58.3% exhibited poor behaviors. Participants had a moderate level of EHL (mean score, 2.30 ± 0.46), with decision-making representing the weakest domain. Insufficient EHL was strongly associated with poor environmental health behaviors (AOR = 8.06, 95% CI: 2.86–10.04; p < 0.001). Additional factors associated with poor environmental health behaviors included consumption of untreated river or other water sources, no physician visit during the previous month, age older than 60 years, and obtaining aquatic foods through self-capture, whereas trade occupation was associated with lower odds of poor behaviors. These findings support community-based EHL programs led by local authorities and public health practitioners that strengthen critical appraisal and decision-making skills, provide accessible and evidence-based information on microplastic risks, and promote practical actions such as reducing single-use plastics and improving household waste management.